Temperature and energy performance of open refrigerated display cabinets using heat pipe shelves. (September 2017) - Jouhara, H.; Nannou, T.; Ghazal, H.; Kayyali, R.; Tassou, S.A.; Lester, S.
Abstract: The paper describes an innovative design of open display cabinet's shelves, based on flat heat pipe technology is presented. Their influence on the energy consumption of the cabinet and their effect on enhancing the preservation conditions of food products are analyzed. The experimental work was carried out using two identical commercial open display cabinets; one cabinet equipped with conventional/commercial shelves while the other one equipped with the new actively-cooled flat heat pipe shelves. Both cabinets were placed inside an ISO-certified environmentally controlled test chamber and experiments were carried out under stable environmental conditions. Food block simulators and real food products were used for the tests. The temperature distribution inside the real food products and the power consumption of the cabinets were measured for the cabinets' set point of 2.0°C. The experimental outcomes were that the use of the heat pipe shelves can homogenize the temperature profile of the products and improve the heat transfer between the cabinet, the shelves and the products. Moreover, the heat pipe shelves facilitated the reduction of the electrical energy consumption of the cabinet by 12% approximately. Finally, a primary of the acidity levels (pH) of the products was conducted. The experiments showed that almost all products placed on the heat pipe shelves, after 20 days of experiments, had almost the same pH values, even 20 days beyond their expiration date.